Pengaruh Komponen Theory of Planned Behavior terhadap Minat Kunjungan Wisatawan pada Wisata Paralayang sebagai Wellness Tourism di Indonesia - Emeralda, Vionika (Jurnal Pariwisata Indonesia, 2025)
Paragliding, while commonly perceived as an extreme adrenaline activity, also offers significant benefits for mental and emotional well-being through experiences of freedom, tranquility, and relaxation in natural settings. This study examines the influence of the three core components of the Theory of Planned Behavior (TPB) attitude, subjective norm, and perceived behavioral control on tourists’ intention to engage in paragliding as part of wellness tourism in Indonesia. A quantitative survey was conducted with 358 respondents who had visited or expressed interest in at least one of 11 paragliding sites across Indonesia. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with Smart PLS 4. Findings reveal that all three TPB components significantly and positively impact visit intention, both individually and collectively. The model explains 69.7% of the variance in tourist intention (R² = 0.697). These results suggest that more positive attitudes, stronger social support, and higher perceived ease of access to paragliding sites enhance tourists’ intention to visit. Keywords: Theory of Planned Behavior (TPB), wellness tourism, tourist intention, paragliding.